Exploring Influence of Communication Campaigns in Promoting Regenerative Farming Through Diminishing Farmers' Resistance to Innovation: An Innovation Resistance Theory Perspective From Global South - Jin, Qiang; Raza, Syed Hassan; Mahmood, Nasir; Zaman, Umer; Saeed, Iqra; Yousaf, Muhammad; Aslam, Shahbaz (Frontiers in Psychology, 2022)
Climate change and farming malpractices (e.g., harmful pesticides use) are harmful to the globe’s productive soil and biodiversity thereby, posing a hazard to the survival of future generations. Innovative technologies are providing continuous smart conservation solutions such as regenerative farming to confront the ongoing climate crisis and maintain biodiversity. Albeit, regenerative farming has the potential to converse climate change by upgrading soil’s organic materials and reinstating biodiversity leading to carbon attenuation. However, a critical problem remains concerning the adaption of conservation farming practices that can assist low-income farmers. In this scenario, theoretical-driven communication campaigns are regarded as critical to addressing individuals’ resistance to innovation. Thereby, this research uncovers the moderating influence of the numerous communication tools in determining the adoption of regenerative farming through diminishing farmers’ resistance to innovation. The study employed a cross-sectional design vis-à-vis survey method. A sample of 863 farmers participated by responding to the self-administrated questionnaire. In line with prior theories, the results of the study identified that communication campaigns such as public service advertisements and scientific informative documentaries can reduce the resistance to innovation that in turn, increases the attitude towards the adoption of regenerative farming with varied intensity. Besides, informational support also remained a significant contributor in determining the intention to adopt regenerative farming. This specifies that implanting habits of conservation farming requires the initiation of communication campaigns using different media content. These results may be advantageous for policymakers to influence farmers' intentions to adopt regenerative farming